PENALARAN DEDUKTIF SISWA SMP DALAM MENYELESAIKAN MASALAH GEOMETRI BERDASARKAN PERBEDAAN GENDER - Afandi, Ahmad (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2016)
This study is aimed to describe deductive reasoning e of Junior High School Students in solving geometry problem based on gender difference. Deductive reasoning in this study refers to general premise, specific premise, conclusion drawing. The subjects of this study are two Junior High School Students. The technique of collecting data applied in this study are task giving and interview. The result of the study would be presented as follows: (1) deductive reasoning e of the male student; at the planning phase for solving problem, subject could formulate general premise and mention the premises which were used to solve the given problem. Subject could also formulate specific premise by giving logical premise referring to general premise based given problem, and he could draw conclusion by determining the strategy firstly to solve the given problem. At the executing planning phase for solving the problem, subject could formulate general premise using premises in order to solve the given problem. Subject could also formulate specific premise by determining logical premise referring to general premise based given problem, and he could draw conclusion using general and specific premise that had been proved. (2) Deductive reasoning e of the female student; at the planning phase for solving problem, subject could formulate general premise by mentioning the premises which were used to solve the given problem. Subject could also formulate specific premise by giving logical premise referring to general premise based given problem, and he could draw conclusion by determining the strategy firstly to solve the given problem. At the executing planning phase for solving the problem, subject could formulate general premise using premises which were used to solve the given problem. Moreover, subject could not formulate specific premises and the way he drew the conclusion was contradictive to the strategy he determined at the planning phase for solving problem.